ANALISIS PENGARUH INFLASI DAN PDRB TERHADAP PENGANGGURAN TERBUKA DI PROVINSI MALUKU (STUDI KASUS KABUPATEN KOTA) - Ali Tutupoho (Jurnal Cita Ekonomika, 2019)
The problem in this study is that open unemployment in Maluku Province has increased, this is a waste of resources and existing potential, can become a burden on family and community problems, the main source of poverty, can encourage increased social unrest and crime and can hinder development. Did inflation and GRDP affect open unemployment in Maluku Province in 2011-2017. This study aims to analyze inflation and GDP against open unemployment in Maluku Province in 2011-2017. The data used is in the form of secondary data obtained from the Central Statistics Agency of Maluku Province. The variables measured are inflation and GRDP as independent variables and Open Unemployment as bound variables. The analysis technique used is the Data Panel. The results showed that the inflation variable had a negative and significant effect on open unemployment in Maluku Province with a sig. 0.0278 and GRDP has a negative and significant effect of 0.0385 on open unemployment in Maluku Province. Taken together, the inflation and GRDP variables have a significant effect on open unemployment in Maluku Province, this can be seen from the F test with a sig. 0.000000. This study explains that the inflation and GRDP variables have a big influence on open unemployment in Maluku Province.